An The Intersection of Islamic Economics and Behavioural Economics: Understanding Consumer Choices in Halla Markets - Intan, Anandhiya; Maisarah, Sausan Nuhaa; Yuliani, Tri Wahyu (LP2M IAIN Palopo, 2025)
This research investigates the intersection of Islamic economics and behavioral economics by examining consumer choices in halal markets across Indonesia, Malaysia, and Pakistan, focusing on halal certification. The study employs qualitative methods, including interviews and surveys with consumers with a total sample of 40, halal certification officials, and firms. Findings reveal significant regional differences in consumer trust, purchasing motivations, and perceptions of halal certification. Indonesian consumers prioritize religious compliance and demonstrate strong trust in local certification bodies, while Malaysian consumers emphasize both religious adherence and global recognition of halal standards. Pakistani consumers balance affordability with compliance but face challenges due to limited public awareness. The research highlights the growing importance of digital verification tools and peer influence in shaping consumer behavior. Challenges such as administrative inefficiencies and inconsistent certification processes are identified. This study contributes novel insights by integrating behavioral economics into Islamic economics research and offers practical recommendations for harmonizing halal certification standards and enhancing consumer trust globally.